2013
DOI: 10.1016/j.transproceed.2013.08.077
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Policies Aimed at Increasing Organ Donation: The Case of Chile

Abstract: Our estimates suggest that these policies have a large cost-saving potential. In fact, considering implementation costs, cost reduction is positive after 4 additional donors pmp, and increasing afterward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…Motivos para essa diferença podem estar relacionados a oferta de leitos hospitalares, leitos de terapia intensiva, especialidade médicas e eventualmente até acordos de transferência inter-regionais de pacientes com enfermidades do sistema nervoso central 15,18 . Porém, novamente, tal estrutura a priori e teoricamente deveria ser oferecida por cada Regional de Saúde.…”
Section: Regional Deunclassified
“…Motivos para essa diferença podem estar relacionados a oferta de leitos hospitalares, leitos de terapia intensiva, especialidade médicas e eventualmente até acordos de transferência inter-regionais de pacientes com enfermidades do sistema nervoso central 15,18 . Porém, novamente, tal estrutura a priori e teoricamente deveria ser oferecida por cada Regional de Saúde.…”
Section: Regional Deunclassified
“…13 A recent systematic review identified economic evaluations surrounding kidney donation and allocation policies. 24 Many such policies have been found to be cost-effective, including developing donation protocols and teams with clearly defined responsibilities within hospitals, [25][26][27] accepting donation after circulatory death (DCD) donors, 28,29 accepting expanded criteria donors, 30 adopting an opt-out model of consent, 31 and accepting donors with potential hepatitis C infection. [32][33][34] In this study, we sought to determine the cost-effectiveness of increasing utilization of kidneys from potential deceased donors with PBM in the Australian setting and to explore how individual patients would be impacted.…”
mentioning
confidence: 99%